Hambatan Implementasi Rekam Medis Elektronik Dengan Metode HOT-Fit di RST Tk.II dr. Soedjono Magelang - Tika Sari Dewi; Ratna Prahesti; Suryo Nugroho Markus (Jurnal Indonesia Sehat, 2024)
Background: Implementation of Electronic Medical Records (EMR) still has many obstacles faced by hospitals. There is a need for a comprehensive EMR evaluation to identify specific problems so that they can be used as a basis for decision making aimed at improving EMR. Purpose: The aim of this research is to exploring barriers to EMR implementation using the Hot-Fit model at RST Tk.II dr. Soedjono Magelang. Method: This research was used the qualitative study type of research with a cross sectional approach. The selected informants were 7 people consisting of the head of the medical records unit, reporting officer, coding officer, registration officer, IT team leader, doctor and nurse and 1 informant as source triangulation, namely the head of medical services.  The data analysis approach uses thematic analysis and the reduction approach uses inductive. Result: This research found 9 themes related to barriers to implementing RME at RST Tk.II dr. Soedjono Magelang, namely officer performance, features and modules, data security, infrastructure, officer behavior, EMR data integration, ease of EMR, information accuracy, and developer/system developer response. Conclusion: There are still identified obstacles to EMR implementation from various aspects. The hospital has made improvements to date so that staff recruitment can increase.